2010
DOI: 10.1016/j.apnu.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Facades of Suffering: Clients' Photo Stories About Mental Illness

Abstract: In this article, photo stories are examined that were the result of working with photography as a therapeutic instrument dealing with suffering in mental health care settings. The purpose is to describe the role of facades in the process of suffering and acceptance. Clients took photographs, talked about them in group meetings, and exhibited them to a broader audience. Their photo stories were analyzed using a mixed-methods model. Data from two narrative approaches (semiotics and hermeneutics) were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 25 publications
0
67
0
1
Order By: Relevance
“…The moral meaning of these illness narratives consists in how patients struggle for authorship over their lifes. This struggle is symbolized in one’s personal narrative [45], reflecting (in the absence of exacerbation or remission of symptoms) quiesecence and homeostasis or an enhanced sense of self-efficay and rekindled aspiration [24, 45]. …”
Section: Introductionmentioning
confidence: 99%
“…The moral meaning of these illness narratives consists in how patients struggle for authorship over their lifes. This struggle is symbolized in one’s personal narrative [45], reflecting (in the absence of exacerbation or remission of symptoms) quiesecence and homeostasis or an enhanced sense of self-efficay and rekindled aspiration [24, 45]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients may keep realistic images of their functioning in daily life and at the same time hold expectations about the future that are based on a more wished‐for life that comes closer to their ideas of their values, as we also found in the photo stories themselves (Sitvast 2010).…”
Section: Resultsmentioning
confidence: 57%
“…Our purpose, however, is to perform a summative evaluation of the photo instrument. In earlier studies, 24,36,40 it has already been described how the intervention works and what the outcomes are. Using a multiplecase design (N = 42) and a hermeneutic semiotic analysis of photo stories, interview texts, and observations, we were able to identify process and structural variables and how they were intrinsically linked up with outcomes (see later).…”
Section: Methodsmentioning
confidence: 95%
“…40 Some 24 participants formulated a new perspective that even 6 to 9 months after finishing the photo group was still held by at least 8 participants (those who were interviewed) and that had led to positive change in daily life in a number of cases. We observed that throughout the proceedings of the photo group sessions the call to express one's values in life and show who you are was picked up by participants and translated in a commitment to give a representation of oneself that almost never was banal and often resulted in a bravely frank testimony.…”
Section: Findings From the Original Studymentioning
confidence: 99%
See 1 more Smart Citation